Arm lymphoedema and upper limb impairments in sentinel node-negative breast cancer patients: A one year follow-up study. (October 2016) - De Groef, An; Van Kampen, Marijke; Tieto, Elena; Schönweger, Petra; Christiaens, Marie-Rose; Neven, Patrick; Geraerts, Inge; Gebruers, Nick; Devoogdt, Nele
Abstract: Purpose: The aim of this study is (1) to investigate the prevalence rate of arm lymphedema, pain, impaired shoulder range of motion, strength and shoulder function one year after a sentinel lymph node biopsy (SLNB) for breast cancer and (2) to determine predictive factors for these complications. Methods: A longitudinal study was performed. One hundred patients with a sentinel-lymph node negative breast cancer were included. All patients were measured before surgery and one year after. Arm lymphedema was measured with the perimeter, pain with the Visual Analogue Scale, shoulder range of motion with an inclinometer, strength with a handheld dynamometer and shoulder function with the Disability of Arm, Shoulder and Hand questionnaire. Patient-, breast cancer- and treatment-related variables were recorded. Results: One year after surgery 8% of sentinel node-negative breast cancer patients had developed arm lymphedema. Fifty percent of patients had pain, 30% had an impaired shoulder range of motion, 8% had a decreased handgrip strength and 49% had an impaired shoulder function. Pain, shoulder range of motion, strength and shoulder dysfunctions changed significantly over one year (p < 0.001). Higher Body Mass Index is a predictive variable for shoulder dysfunctions one year post-SLNB. Conclusions: Prevalence rate of lymphedema and other upper limb impairments may not be underestimated after SLNB. Pain, shoulder range of motion, handgrip strength and shoulder function change significantly up to one year compared to preoperative values in sentinel node-negative breast cancer patients. Highlights: Up to 8% of sentinel node-negative breast cancer patients develop lymphedema in the first year after surgery. Prevalence rates of pain, impaired shoulder range of motion and handgrip strength should not be underestimated after the sentinel node biopsy. Weight control after the sentinel lymph node biopsy is important since higher BMI is a risk factor for shoulder dysfunctions.